2022
DOI: 10.2174/0929867328666210628143430
|View full text |Cite
|
Sign up to set email alerts
|

HuR as Therapeutic Target in Cancer: What the Future Holds

Abstract: : ELAV-like protein 1, or HuR (human antigen R), is an RNA-binding protein encoded by the ELAVL1 gene in humans. One of its best functions is to stabilize mRNAs in order to regulate gene expression. HuR protein overexpression has undoubtedly been linked to an increased risk of tumor growth, progression, and metastasis, rendering it a potential therapeutic target candidate in cancer. Novel agents interfering with HuR expression have been tested, both in vitro and in vivo, with promising results. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Before ELAVL1 was recognized as an m6A regulator, ELAVL1, as a traditional RNA-binding protein, was found to be involved in the occurrence and progression of almost all tumors ( 58 , 59 ). With the development of m6A research, ELAVL1, as an m6A regulator, was found to interact with other m6A regulators to regulate RNA metabolism ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Before ELAVL1 was recognized as an m6A regulator, ELAVL1, as a traditional RNA-binding protein, was found to be involved in the occurrence and progression of almost all tumors ( 58 , 59 ). With the development of m6A research, ELAVL1, as an m6A regulator, was found to interact with other m6A regulators to regulate RNA metabolism ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs regulating HuR expression have been identified in human cancers. Although HuR expression is increased in most neoplasms [ 160 ], this knowledge is limited to certain types of cancers and has essentially been demonstrated in vitro using cancer cell lines.…”
Section: Mirnas-regulating Hur and Ttp Family Membersmentioning
confidence: 99%
“…HuR overexpression has been repeatedly linked to malignant transformation, and increased nuclear/cytoplasmic HuR expression has been associated with patients' prognosis in different malignancies [21]. The above-mentioned properties advocate for the adverse clinical outcomes related to HuR protein overexpression in various cancer types, including advanced stage, positive lymph nodes and poor survival [22][23][24][25][26][27].…”
Section: Hur and Neoplasiamentioning
confidence: 99%
“…Many different strategies have been used in an attempt to modify or suppress HuR's action in cancer [27], including inhibiting its cytoplasmic translocation, decreasing its expression via siRNAs or inhibiting its binding to target mRNAs. On top of that, intense research has been performed to obtain data regarding the synergistic use of HuR inhibition with chemotherapeutic and a variety of other agents [53][54][55][56][57] (Figure 2, Table 1).…”
Section: Agents Interacting With Hur Expression and How Hur's Inhibition Could Affect Tumor Progressionmentioning
confidence: 99%